2010
DOI: 10.1590/s1806-83242010000200003
|View full text |Cite
|
Sign up to set email alerts
|

Use of chewing gum containing 15% of xylitol and reduction in mutans streptococci salivary levels

Abstract: Frequent use of Xylitol may decrease the S. mutans levels. However, very little is known about whether this effect on the levels of cariogenic bacteria is maintained after the interruption of short-term usage of xylitol. This study aimed at evaluating changes in mutans streptococci (MS) salivary levels after using a chewing gum containing xylitol. Twelve volunteers harboring ≥ 10 5 CFU MS/ml saliva levels were asked to chew Happydent-xylit  for 5 minutes, 5 X/day, for 30 days. Saliva samples were collected at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
3
8
0
3
Order By: Relevance
“…Another Chinese study reported that maltitol chewing gum may lead to similar reduction of dental plaque as xylitol chewing gum (Li, 2010). Several recent studies have confirmed the generally accepted idea that xylitol exerts a special growth-retarding effect on MS (Ribelles et al, 2010;Paula et al, 2010;Fraga et al, 2010;Duane, 2010;Söderling et al, 2011;Campus et al, 2011). The study by Duane (2010) demonstrated that children receiving 4.24 g xylitol daily (in five chewing episodes) in the form of chewing gum showed reduced bacterial counts even when the gum contained hexose-based polyols.…”
Section: Effect Of Alditols On Oral Bacterial Counts and Dental Plaquementioning
confidence: 69%
“…Another Chinese study reported that maltitol chewing gum may lead to similar reduction of dental plaque as xylitol chewing gum (Li, 2010). Several recent studies have confirmed the generally accepted idea that xylitol exerts a special growth-retarding effect on MS (Ribelles et al, 2010;Paula et al, 2010;Fraga et al, 2010;Duane, 2010;Söderling et al, 2011;Campus et al, 2011). The study by Duane (2010) demonstrated that children receiving 4.24 g xylitol daily (in five chewing episodes) in the form of chewing gum showed reduced bacterial counts even when the gum contained hexose-based polyols.…”
Section: Effect Of Alditols On Oral Bacterial Counts and Dental Plaquementioning
confidence: 69%
“…Bleeding from the gums during probing in individuals applying chewing gum with xylitol increased by 0.26; in individuals not using chewing gum -by 0.36 [30]. According to Fraga et al [31], a high frequency (5 times a day) of applying chewing gum containing 15% of xylitol, despite the low daily total intake of xylitol (1 g), depletes the amount of SM in saliva. After 30 days of discontinuation, a decrease in the count of SM in saliva was noted, compared to the first evaluation where SM ≥ 10 5 CFU mL/saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Dabei nehmen die Bakterien Xylit zwar in demselben Ausmaß wie normale Saccharose auf, sie sind aber nicht in der Lage, diese Substanz zu verstoffwechseln und daraus Energie zu gewinnen. So reduzierte sich durch einen regelmäßigen Xylitverzehr die Anzahl der Mutans-Streptokokken im Speichel und in den Plaquebelägen [25,26,27]. Die Aufnahme erfolgte oftmals über xylithaltige Kaugummis, wobei diese Maßnahme in einer Studie von Alamoudi et al [26] einen weitaus größeren kariespräventiven Effekt hatte als die Flouridprophylaxe.…”
Section: Omega-3-fettsäuren Hemmen Entzündungsprozesseunclassified